1995
DOI: 10.1007/bf00225073
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of the apo ?4 allele in Khoi San from South Africa

Abstract: Variation at the apolipoprotein E (apo E) gene locus affects cholesterol concentrations, the risk for atherosclerosis and Alzheimer disease (AD), and is associated with longevity in Caucasians. We have determined apo E gene frequencies and effects on cholesterol levels in Khoi San (Bushmen) from South Africa. The frequency of the apo epsilon 4 allele (0.37), which confers dose-dependent susceptibility to atherosclerosis and AD in Caucasians, was twice as high, and apo E4 homozygotes were 3-5 fold more frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 15 publications
6
21
0
1
Order By: Relevance
“…In the present study, associations of APOE genotypes with serum lipids were consistent with the well-identified effects of APOE (33)(34)(35). Several studies have shown that the effect of E*2 in reducing cholesterol levels is two-to four-fold the increasing effect of E*4 (4,5,36), whereas similar effects of both alleles have also been reported (37,38). In Brazilian Caucasians the influence of E*2 was greater than that of E*4.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, associations of APOE genotypes with serum lipids were consistent with the well-identified effects of APOE (33)(34)(35). Several studies have shown that the effect of E*2 in reducing cholesterol levels is two-to four-fold the increasing effect of E*4 (4,5,36), whereas similar effects of both alleles have also been reported (37,38). In Brazilian Caucasians the influence of E*2 was greater than that of E*4.…”
Section: Discussionsupporting
confidence: 91%
“…However, African Americans have as high a prevalence of AD as other Americans and Western peoples [25,33]. The association between apoE genotype and cholesterol concentration may be the result of a Western lifestyle since no association was found in an African Bushmen population with low plasma cholesterol [34]. Similarly, there seems to be no association between the Â4 allele and AD in native Africans [35] although this association was substantial in elderly African Americans [36].…”
Section: Discussionmentioning
confidence: 84%
“…The apoe3 allele is particularly advantageous in communities where agriculture has been established for a long time. Therefore it is not surprising to find the e4 allele in high frequencies in South African black populations and among the Khoi San, as South African blacks are believed to be more ancient than Caucasians [19] and the Khoi San are one of the oldest populations known [25], being the oldest inhabitants of Southern Africa where they are believed to have lived for at least 20,000 years. Originally hunter-gatherers, most Khoi San now live in settlements.…”
Section: Discussionmentioning
confidence: 99%